The components and indicators of professional learning community: the guidelines for educational quality improvement - Klinthaisong, Korakeng; Ketchatturat, Jatuphum; Samat, Charuni (Institute of Advanced Engineering and Science, 2025)
A professional learning community (PLC) is a group of educational personnel who come together to exchange knowledge, develop, and collaboratively solve problems related to improving instructional practices and school issues. The common goal is to develop students’ competencies. PLCs have the potential to transform the quality of educational results significantly. Consequently, studying the components and indicators of a PLC and conducting confirmatory factor analysis (CFA) of PLC models can help schools understand the key factors and practices that contribute to PLC success. This knowledge can be applied to develop a strong PLC within the school. The study of components and indicators of the PLC is exploratory research. The samples consisted of 1,080 administrators and heads of the subject group from 120 schools under the Secondary Educational Service Area Office, randomized by multi-stage random sampling. The research tool was a 4-level rating scale questionnaire. Research findings indicate that the CFA of PLCs aligns with empirical evidence. All components in the PLC model have significant factor loadings ranging from 0.916 to 0.945 at the 0.01 level (p<0.01). When ranked from highest to lowest, these components are: i) supportive conditions–structures; ii) shared values and vision; iii) collective learning and application; iv) Shared and supportive leadership; v) supportive conditions–relationships; and vi) shared personal practice. All of these are essential components of a PLC and serve as an important mechanism for educational personnel to work together to improve the quality of schools.